The effect of using analogies to integrate system dynamics concepts in accounting education - Baptista, L.; Lourenço, I.; Simões, E. (Accounting Education, 2024)
This paper analyses whether using analogies to integrate knowledge from other scientific areas increases the level of accounting knowledge. We defined two sets of analogies, one between the physical states of water and the economic and cash flows, and another between the concepts of stock, flow and feedback that were taken from the System Dynamics field and the financial statements. An experimental study was conducted with students from a European university, who participated in an accounting revision class. The grades of the students who attended the revision class using the analogies were higher than of those who did not attend this class. These findings reinforce the power of analogies as a useful tool and validate the benefits of integrating knowledge from other areas in accounting education.